Developmental Aggregation of Myxococcus xanthus Requires frgA, an frz-Related Gene - Cho, Kyungyun (American Society for Microbiology, 2000)
Myxococcus xanthus is a gram-negative bacterium which has a complex life cycle that includes multicellular fruiting body formation. Frizzy mutants are characterized by the formation of tangled filaments instead of hemispherical fruiting bodies on fruiting agar. Mutations in the frz genes have been shown to cause defects in directed motility, which is essential for both vegetative swarming and fruiting body formation. In this paper, we report the discovery of a new gene, called frgA (for frz-related gene), which confers a subset of the frizzy phenotype when mutated. The frgA null mutant showed reduced swarming and the formation of frizzy aggregates on fruiting agar. However, this mutant still displayed directed motility in a spatial chemotaxis assay, whereas the majority of frz mutants fail to show directed movements in this assay. Furthermore, the frizzy phenotype of the frgA mutant could be complemented extracellularly by wild-type cells or strains carrying non-frz mutations. The phenotype of the frgA mutant is similar to that of the abcA mutant and suggests that both of these mutants could be defective in the production or export of extracellular signals required for fruiting body formation rather than in the sensing of such extracellular signals. The frgA gene encodes a large protein of 883 amino acids which lacks homologues in the databases. The frgA gene is part of an operon which includes two additional genes, frgB and frgC. The frgB gene encodes a putative histidine protein kinase, and the frgC gene encodes a putative response regulator. The frgB and frgC null mutants, however, formed wild-type fruiting bodies.